Językoznawcza i logopedyczna analiza syntetycznej metody wywoływania zębowej głoski zwarto-szczelinowej - Pluta-Wojciechowska, Danuta (Forum Lingwistyczne, 2016)
The Linguistic Analysis and the Analysis from the Perspective of Speech Therapy of the Synthetic Method of Elicitation of the Dental Affricative Sound The author Danuta Pluta-Wojciechowska presents certain reflections on the methods of sound elicitation. She offers the linguistic analysis, as well as, the analysis from the point of view of speech therapy of the synthetic method of sound learning providing, at same time, the example of therapy where professionals dealt with case of dental affricative sound. In the following section of the text, the relevance of linguistic knowledge and the theory of speech therapy in the course of planning the providing speech treatment was stressed. Key words: dyslalia, phonetics, speech therapy, sound elicitation<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />